Comparative Analysis of Forecasting Methods to Increase Condotel Accommodation Sales on ApVoucher - Tika Putri Nur Huda; Dudi Haryadi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Tourism is a key driver of economic growth, supported by the accommodation sector, including innovations such as condotels like ApVoucher that combine apartment and hotel functions. However, due to unpredictable sales fluctuations and intense competition, companies need proper planning, with sales forecasting playing an important role in estimating future sales. This study Aims to analyze and compare the level of accuracy for increasing sales to help in preparing plans and reducing demand uncertainty. The forecasting method used is the moving average method that works by averaging previous data to produce a stable pattern and the exponential smoothing method that works by giving greater weight to the latest data so that it is more responsive to changes. The study used a population in the form of historical data on condotel (Hotel) sales by applying the 3-month moving average method and the exponential smoothing method with a constant of 0>1. The analysis was carried out to determine the error rate value through the Mean Absolute Deviation (MAD) and Mean Squared Error (MSE). The research results show that the moving average method is more effective in sales conditions that tend to be stable by producing lower accuracy values. This shows that the effectiveness of the method is influenced by data characteristics.